MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PEKERJAAN STRUKTUR BAWAH DAN STRUKTUR ATAS GEDUNG BERTINGKAT - Beryl Adityanto; Sony Irawan; Jati Utomo Dwi Hatmoko; Frida Kistiani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Safety and health problems in Indonesia is still underestimated, as it is evident from the number of place accidents that occur mainly in the construction sector. Based on the report of the International Labor Organitation (ILO), every day of work accidents resulting in as many as 6,000 cases of fatal victims. While in Indonesia there are 20 fatal accidents in every 100 thousand workers in the construction sector (Reuters, Tuesday, January 15, 2013).This research will examine on safety and health hazard identification, risk assessment and how to control safety and health risks that exist on the work of bottom and top structure of high rise building construction, methods of assessment using the risk assessment matrix derived from the NHS Highland adopted by AS / NZS 4360: 2004 Risk Management. From the results of this study obtained that were classified as high risk amounted to 7 risk (11.67%), medium risk amounted to 43 risk (71.67%) and low risk amounted to 10 risk (16.67%). Seven risk categories of high risk is the risk of falling from a height while preparing formwork beams and floor plate with a risk index of 14.36, workers buried by an avalanche while excavation work with a risk index of 12.67, falling from a height due to timber formwork porous material with a risk index of 11.55, fell from a height while the preparation of scaffolds with a risk index of 11.22, risk of falling material while lifting material with a risk index of 11.02, electric shock when excavation work with a risk index of 10.49 and risk of falling from height when installing formwork column with a risk index of 10.36. from identification and assessment risk found that top structure of high rise building construction has more risk and average risk index greater than under structure of high rise building construction.